2001
DOI: 10.1152/ajpheart.2001.281.2.h552
|View full text |Cite
|
Sign up to set email alerts
|

O2-dependent prostanoid synthesis activates functional PGE receptors on corpus cavernosum smooth muscle

Abstract: We have previously demonstrated that decreased O2 tension inhibits prostaglandin synthesis from human corpus cavernosum smooth muscle cells in static culture over 8-18 h (R. B. Moreland et al., Molecular Urology 2: 41-47, 1998). In this report, an experimental system was designed that allowed determination of the effects of O2 tension changes over the time frame of physiological penile erection. Human corpus cavernosum smooth muscle cells were cultured on microcarrier beads in enclosed stirrer flasks so that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 30 publications
(55 reference statements)
1
55
0
1
Order By: Relevance
“…2 We have previously demonstrated that PGE 1 causes cAMP levels to increase to 750 -1000 pmol=mg protein in human cavernosal smooth muscle cells through either the EP2 and=or EP4 receptors. 12,16 This PGE 1 -induced increase in cAMP synthesis was observed to be proportional to the relaxation response. In contrast, the induction of cAMP synthesis by BW245C in the present study appears much less robust than the efficacy of DP agonists on smooth muscle relaxation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…2 We have previously demonstrated that PGE 1 causes cAMP levels to increase to 750 -1000 pmol=mg protein in human cavernosal smooth muscle cells through either the EP2 and=or EP4 receptors. 12,16 This PGE 1 -induced increase in cAMP synthesis was observed to be proportional to the relaxation response. In contrast, the induction of cAMP synthesis by BW245C in the present study appears much less robust than the efficacy of DP agonists on smooth muscle relaxation.…”
Section: Discussionmentioning
confidence: 93%
“…Human corpus cavernosum smooth muscle cells were grown from tissue explants 17 and cultured on Cytodex TM III microcarrier beads (Pharmacia, Piscataway, NJ), as previously described for human corpus cavernosum smooth muscle cells 12 and human umbilical endothelial cells. 19 Cells were grown and maintained under low shear conditions at media PO 2 corresponding to blood PO 2 during penile erection (100 mm Hg).…”
Section: Pgd 2 Synthesis By Human Corpus Cavernosum Smooth Muscle Cellsmentioning
confidence: 99%
“…We have previously demonstrated the expression of EP2 and EP4 receptors in HCC and in cultured SMC using RT-PCR. 6 We were not successful in demonstrating EP1 receptor mRNA expression either by RNase protection or RT-PCR (data not shown) despite pharmacologic functional evidence suggesting the presence of these receptors (see below).…”
Section: Expression Of Ep2 and Ep3 Receptor Mrna In Hccmentioning
confidence: 87%
“…4,5 In addition, corpus cavernosum smooth muscle cells (SMC) in culture have been shown to synthesize PGD 2 , PGE 2 and PGF 2a , all of which are regulated by oxygen tension. 6 Of these eicosanoids, only PGE 1 has been reported to relax penile cavernosal smooth muscle. [7][8][9][10] Further, arachidonic acid, the precursor of PGE 2 , can relax human corpus cavernosum (HCC) smooth muscle in the presence of thromboxane receptor antagonists, a process blocked by the prostaglandin G/H synthase inhibitor indomethacin.…”
Section: Introductionmentioning
confidence: 99%
“…They have found the expression of EP2, EP3I and EP3II receptor mRNA; however, the expression of EP1 and EP4 receptor mRNA was not determined. But before, Moreland et al 15 reported that human corpus cavernosum express both EP2 and EP4 receptor mRNA. In addition, there are eight isoforms of EP3 receptor.…”
Section: Discussionmentioning
confidence: 99%